2019
DOI: 10.1177/0333102419864507
|View full text |Cite
|
Sign up to set email alerts
|

PACAP27 induces migraine-like attacks in migraine patients

Abstract: Introduction Pituitary adenylate cyclase-activating polypeptide (PACAP) is found in two functional isoforms, namely PACAP38 and PACAP27. The migraine-inducing properties of PACAP38 are well studied. However, it is not known whether the lesser-known and under-studied protein isoform, PACAP27, can also induce migraine attacks. Here, we studied the effect of human PACAP27 infusion on induction of migraine in a provocation model. Methods In a crossover study, 20 migraine without aura patients were randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 46 publications
3
66
0
Order By: Relevance
“…Of these, 27 studies met the inclusion criteria (1994 and 2020) and were included in the qualitative and quantitative analysis (935) (Figure 1). Twelve studies (10 published and two studies under review) reported data on the incidence of migraine attacks after placebo in individuals with migraine without aura (917,31,33), whereas 10 studies did so in healthy volunteers (18,19,22,23,25,27,29,30,32,34). Furthermore, 16 studies reported data on the incidence of delayed headache after placebo in healthy volunteers (13,1830,32,34).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 27 studies met the inclusion criteria (1994 and 2020) and were included in the qualitative and quantitative analysis (935) (Figure 1). Twelve studies (10 published and two studies under review) reported data on the incidence of migraine attacks after placebo in individuals with migraine without aura (917,31,33), whereas 10 studies did so in healthy volunteers (18,19,22,23,25,27,29,30,32,34). Furthermore, 16 studies reported data on the incidence of delayed headache after placebo in healthy volunteers (13,1830,32,34).…”
Section: Resultsmentioning
confidence: 99%
“…• To utilize anti-PACAP drugs in migraine prophylaxis, their longterm safety must be examined and clarified. Moreover, their advantages should be compared with those of the anti-CGRP monoclonal antibodies that are available patients provoked in a crossover study significantly more migraine-like attacks than placebo, further strengthening the role of PACAP in the pathogenesis of migraine [39].…”
Section: Article Highlightsmentioning
confidence: 99%
“…Most participants reported facial flushing and puffiness persisting over 24 h post PACAP38 infusion. PACAP is found in human skin [53] and PACAP infusion causes intense facial flushing [21].…”
Section: Discussionmentioning
confidence: 99%